Peran Kreativitas Dalam Membentuk Strategi Coping Mahasiswa Ditinjau Dari Tipe Kepribadian Dan Gaya Belajar - Pratitis, Niken Titi (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. This study aims to determine the effect of creativity in shaping the student coping strategy mainly by distinguishing personality type (ie based on the type of Dominance, Influence, Steadiness and Complience and differentiate learning styles (ie visual learning style, auditory and kinestesik). Variables consisted of variables depending Strategy coping and three independent variables, namely Creativity, Personality Types and Learning Styles. models are quantitative study with 38 study subjects at the end of the semester students of the Faculty of Psychology, University of Surabaya August 17, 1945. research data retrieval is done by deploying scale two of them made by a team of researchers and one scale using standard scales that have proven validity reliability. regression analysis by ANOVA using SPSS version 20 ( IBM version) shows that creativity plays a role in shaping the individual coping strategies. separately but not learning styles play a role in shaping the coping strategies despite a role in creativity individuals, where the t-test results illustrate that there are significant differences in creativity between the visual and auditory learning styles. opposite, personality type does not affect creativity but affect the individual coping strategies, although the results of the t test shows that only dominance and Steadiness personality and influence by complience which have significant differences in coping strategies.Keywords : Coping Strategies , Creativity , Personality Types , Learning Styles